2019
DOI: 10.1002/adsc.201901314
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine(III)‐Promoted Rapid Cascade Reaction of Quinoxalinones with Unactivated Alkenes and TMSN3

Abstract: The first example of rapidly three‐component cascade reaction of quinoxalinones with unactivated alkenes and TMSN3 under mild condition has been described. This approach provides a practical solution for the rapid modification of quinoxalinones and enables new planning strategies for the synthesis of bioactive organoazides. A radical mechanism is responsible for this three‐component transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 85 publications
0
26
0
1
Order By: Relevance
“…Based on the above experimental results and previous reports (Yi et al, 2017 ; Yan et al, 2019 ; Shen et al, 2020 ), a probable radical mechanism for the three-component reaction was proposed ( Scheme 4 ). First, deuterium radical ( A ) was generated from NaBD 4 in the presence of Fe(III).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Based on the above experimental results and previous reports (Yi et al, 2017 ; Yan et al, 2019 ; Shen et al, 2020 ), a probable radical mechanism for the three-component reaction was proposed ( Scheme 4 ). First, deuterium radical ( A ) was generated from NaBD 4 in the presence of Fe(III).…”
Section: Resultsmentioning
confidence: 52%
“…We also achieved a useful method for the rapid synthesis of quinoxalinone-containing organoazides using three-component cascade reaction of quinoxalinones with olefins and TMSN 3 (Shen et al, 2020 ). Keeping on our interests in developing simple and efficient methods for the synthesis of quinoxalinones (Xu et al, 2019 ; Zhang H. et al, 2019 ; Shen et al, 2020 ), herein, we demonstrated a radical-type three-component deuteration of quinoxalinones with olefins and NaBD 4 mediated by Fe(NO 3 ) 3 ∙9H 2 O for the first time ( Scheme 1C ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Zhang's group developed a hypervalent iodine(III)-promoted three-component alkylation of quinoxalin-2(1 H )-ones with unactivated alkenes and TMSN 3 ( Figure 1B , Equation h) (Shen et al, 2020 ). This method provides a step-economical solution for the introduction of β-azido alkyl groups into the quinoxalin-2(1 H )-ones to rapidly synthesize bioactive organoazides.…”
Section: Three-component C–h Alkylation Of Quinoxalin-2(1 Hmentioning
confidence: 99%
“…Because of their synthetic usefulness and potential biological importance, the introduction of functional groups into the C3-position of the quinoxalin-2(1 H )-ones has already become a research hotspot, and various protocols for the direct C3-H functionalization of quinoxalin-2(1 H )-ones have been reported (Ebersol et al, 2019 ; Gu et al, 2019 ; Hong et al, 2019 ; Li et al, 2019 ; Peng et al, 2019 ; Rostoll-Berenguer et al, 2019 ; Teng et al, 2019 ; Wang et al, 2019a , 2020 ; Xie et al, 2019b ; Zhao et al, 2019 ; Zheng and Studer, 2019 ; Tian et al, 2020 ; Yuan et al, 2020 ). In particular, the C3-H functionalization of quinoxalin-2(1 H )-ones involving hypervalent iodine reagents has drawn wide attention for the aforementioned advantages of hypervalent iodine reagents, mainly including arylation (Paul et al, 2017 ; Yin and Zhang, 2017 ), trifluoromethylation (Wang et al, 2018 ; Xue et al, 2019a ), alkylation (Wang et al, 2019b ; Xie et al, 2019a ; Xue et al, 2019b ; Shen et al, 2020 ), and alkoxylation (Xu et al, 2019 ; Yang et al, 2019 ) of quinoxalin-2(1 H )-ones, which provide convenient and environmentally friendly means for the synthesis of 3-substituted quinoxalinone derivatives. In this mini review, we will focus on the progress being made in the direct C3-H functionalization of quinoxalin-2(1 H )-ones involving the hypervalent iodine reagents and discuss their mechanisms, in order to inspire more applications of hypervalent iodine reagents in related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Dipankar Koley' group explored a strategy to synthesize α-sulfono-β-heteroaryl scaffolds using alkenes with aryl sulfinic acids and quinoxalin-2(1H)-ones (Scheme 1B) (Sekhar Dutta et al, 2019). Afterwards, Pengfei Zhang' group reported a hypervalent Iodine(III)-promoted rapid cascade reaction of quinoxalinones with unactivated alkenes and TMSN 3 (Scheme 1C) (Shen et al, 2019). Recently, Wei Wei' group synthesize 3-trifluoroalkylated quinoxalin-2(1H)-ones via K 2 S 2 O 8 -mediated unactivated alkenes with quinoxalin-2(1H)-ones and CF 3 SO 2 Na (Scheme 1D) (Meng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%